Histological profile of collagen fibers on Bligon goat skin soaked in weak acids and bases solution at different concentration (Jurnal Ilmu dan Teknologi Hasil Ternak, 2013)
Strong acids and bases has been widely applied in commercial gelatin industry, but the application of weak acids and bases has not been much done. Application of a solution of strong acids and bases could be expected to affect human health and uneconomical, therefore it requires further study on the possibility of the their application in the production process of gelatin. Quantity and quality of gelatin associated with changes in their structure of collagen fibers. Research has been conducted on the histological profile of collagen fibers from Bligon goat skin soaked in weak acids and bases. Weak acid (CH3COOH 0.5 M) and weak base (Ca(OH)2 100 g/L) was used as a soak solution, each of which was made into three concentration levels (3, 6 and 9% v/v).Â  Samples of skin composites made duplo size 3x3 cm and each soaked for 4 days and were then made histological preparations. Subsequent histological profiles were analyzed descriptively. Results showed that the changes in the structure of skin collagen fibers in CH3COOH 0.5 M more significant than Ca(OH)2 100 g/L and control (without soaked) for the same level of concentration.Key words: Histological, collagen fibers, bligon goat skin, weak acids and bases